2013
DOI: 10.1182/blood-2012-12-471680
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric assessment predicts survival for older adults receiving induction chemotherapy for acute myelogenous leukemia

Abstract: Key Points Geriatric assessment, with a focus on cognitive and physical function, improves prediction of survival among older adults treated for AML. Use of geriatric assessment may inform trial design and interventions to improve outcomes for older adults with AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
277
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(290 citation statements)
references
References 68 publications
8
277
2
3
Order By: Relevance
“…This result is concordant with other studies that have demonstrated that older cancer patients with cognitive impairment have a higher risk of death compared to those with normal cognitive function (28)(29)(30). These results can be easily explained.…”
Section: Discussionsupporting
confidence: 92%
“…This result is concordant with other studies that have demonstrated that older cancer patients with cognitive impairment have a higher risk of death compared to those with normal cognitive function (28)(29)(30). These results can be easily explained.…”
Section: Discussionsupporting
confidence: 92%
“…Although assessment of risk of treatment-related mortality (TRM) after intensive therapy is usually most relevant in older patients (commonly above the age of 65 years), age is merely one, and not the most important, predictor of TRM. [130][131][132][133][134][135] Furthermore, TRM rates are declining due to improved supportive care and to better health status in older patients. 136,137 Therefore, age alone should not be the decisive determinant to guide therapy.…”
Section: Current Therapymentioning
confidence: 99%
“…Several risk scoring systems are available that use patient-specific and diseasespecific factors to make the choice of intensive or alternative treatment. 74,132,133,210 The relevance of systems 193,194 originally designed to forecast NRM after allogeneic HCT is under investigation. 211 Treatment alternatives for unfit patients are limited to best supportive care, low-intensity treatment, or clinical trials with investigational drugs.…”
Section: -209mentioning
confidence: 99%
“…35 These impairment were independently associated with worse outcomes in patients with cancer. [38][39][40][41][42] Second, geriatric assessment can predict survival and adverse events of treatment to assist clinical decision making. Treatment decisions in older patients with cancer can be challenging, as other comorbid conditions may limit life expectancy and the ability to tolerate oncologic treatment.…”
Section: Why Perform a Geriatric Assessment?mentioning
confidence: 99%